Culex pipiens complex with three new Records in Bangladesh: A new challenge to the elimination of Lymphatic filariasis (Bangladesh Journal of Zoology, 2024)
The current study in Gulshan thana area of Dhaka North City Corporation documented new records of the members of Culex pipiens group. Until now, Culex quinquefasciatus was recorded as the sole known species of pipiens group in Bangladesh. Through morphological, wing morphometry and genetic analysis, some members of the Culex pipiens complex were identified, such as, Culex pipiens, Culex pipiens pallens, and Culex pipiens f pipiens. These species were observed co-existing with Cx. quinquefasciatus. Molecular identification was conducted by employing cytochrome c oxidase subunit 1 (COI) and 16S rRNA gene barcoding including sequence percentage identity using BLAST and performing tree-based identification through Neighbor-Joining (NJ) model using the MEGA 11 software package. The 16S sequences of Cx. pipiens pallens and Cx. pipiens f pipiens were submitted for the first time into the GenBank. This study also represents the first record of Cx. pipiens pallens in the Indian region, a species previously documented primarily in Japan, China and South Korea as a prevalent house mosquito.  Moreover, the fact that all the newly recorded species are well known vectors of filariasis poses a substantial challenge to Bangladesh, which has recently been declared as a filaria-free country by World Health Organization.Bangladesh J. Zool. 52(1): 95-110, 2024